The low-temperature heat capacity of fullerite C60 - Bagatskii М.I.; Sumarokov, V.V.; Barabashko, M.S.; Dolbin, A.V.; Sundqvist, B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The heat capacity at constant pressure of fullerite C60 has been investigated using an adiabatic calorimeter in a temperature range from 1.2 to 120 K. Our results and literature data have been analyzed in a temperature interval from 0.2 to 300 K. The contributions of the intramolecular and lattice vibrations into the heat capacity of C60 have been separated. The contribution of the intramolecular vibration becomes significant above 50 K. Below 2.3 K the experimental temperature dependence of the heat capacity of C60 is described by the linear and cubic terms. The limiting Debye temperature at T → 0 K has been estimated (Θ0 = 84.4 K). In the interval from 1.2 to 30 K the experimental curve of the heat capacity of C60 describes the contributions of rotational tunnel levels, translational vibrations (in the Debye model with Θ0 = 84.4 K), and librations (in the Einstein model with ΘE,lib = 32.5 K). It is shown that the experimental temperature dependences of heat capacity and thermal expansion are proportional in the region from 5 to 60 K. The contribution of the cooperative processes of orientational disordering becomes appreciable above 180 K. In the high-temperature phase the lattice heat capacity at constant volume is close to 4.5 R, which corresponds to the high-temperature limit of translational vibrations (3 R) and the near-free rotational motion of C60 molecules (1.5 R).